2018
DOI: 10.1007/s00192-018-3594-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of solifenacin on postvoid dribbling in women: results of a randomized, double-blind placebo-controlled trial

Abstract: There were no differences in PVD outcomes between the solifenacin and placebo groups. Solifenacin may play a role in treating women with the most severe symptoms. Because of the powerful placebo response seen in this study, behavior-based interventions may be useful for treating PVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Antibiotics, the most common therapy used in clinical practice, may help symptomatic remission, but the efficacy is not durable. Alpha blockers or anticholinergics are effective for treating LUTS associated with benign prostatic hyperplasia, but they cannot play a similar role in treating women with LUTS . New treatments are being explored.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics, the most common therapy used in clinical practice, may help symptomatic remission, but the efficacy is not durable. Alpha blockers or anticholinergics are effective for treating LUTS associated with benign prostatic hyperplasia, but they cannot play a similar role in treating women with LUTS . New treatments are being explored.…”
Section: Discussionmentioning
confidence: 99%
“…One trial found that, for patients with UUI plus more severe/common postvoid dribbling, anticholinergics resulted in greater reduction of postvoid dribbling episodes compared with placebo. 6 In Ablove's postmenopausal patients, postvoid dribbling also showed an association with age, body mass index, and the length of the genital hiatus. 5 Although some have speculated that postvoid dribbling may result from pelvic floor weakness, indicating a presumed increase with age, 2 Ablove 5 actually suggested a decreased incidence of postvoid dribble with increasing age.…”
Section: Discussionmentioning
confidence: 98%
“…Similar to our study's findings, in Ablove's premenopausal and perimenopausal patients, postvoid dribbling was associated with UUI. One trial found that, for patients with UUI plus more severe/common postvoid dribbling, anticholinergics resulted in greater reduction of postvoid dribbling episodes compared with placebo 6 . In Ablove's postmenopausal patients, postvoid dribbling also showed an association with age, body mass index, and the length of the genital hiatus 5 .…”
Section: Discussionmentioning
confidence: 99%